P073: Consultations in the emergency department: a systematic review. (May 2019) - Kirkland, S.; Gaudet, L.; Keto-Lambert, D.; Rowe, B.
Abstract : Introduction : While consultation is a common and important aspect of emergency department (ED) care, a previous systematic review identified significant utilization and process variation across ED's. The aim of this review update was to examine the proportion of the patients undergoing consultation in the ED among recent studies.Methods : Eight primary literature databases and the grey literature were searched. Studies published from 2007 to 2018 focusing on all-comers to the ED and reporting a consultation-related outcome were included. Disease- and specialty-specific studies were not eligible. Two independent reviewers screened studies for relevance, inclusion, quality assessment, and data extraction. Disagreements were resolved through consensus. Means, medians and interquartile ranges are reported. Wilcoxon-rank sum test and one-way ANOVA were used to identify differences between groups, as appropriate.Results : A total of 2632 unique citations and 49 studies from the grey literature were screened, of which 29 primary studies were included. Fifteen studies reported on the proportion of ED patients undergoing consultation, involving EDs in the Middle East (n = 4), North America (n = 4), Asia (n = 4), and Europe (n = 3). Overall, the proportion of patients receiving consultation ranged from 7% to 78% (median: 26%; IQR: 20%, 38%). There were no differences in the proportions of consulted patients based on country of origin. Ten studies were conducted prior to 2013, while five studies recruited patients during and after 2013. The mean proportion of consulted patients was lower for post-2012 studies compared to pre-2012 studies (mean: 18% vs. 36%; p = 0.0048). The proportion of consulted patients admitted to hospital ranged considerably between the 14 reporting studies (median: 56%; IQR: 49%, 76%). No differences in the proportion of admitted patients undergoing a consult were identified based on country of origin or year of recruitment for the study.Conclusion : Although consultation utilization appears to be decreasing overall, there is considerable practice variation in EDs around the world. These differences may result from variation in patient acuity, case-load, staffing levels, institutional and health-system organization, and medical training and future research should explore reasons for these differences.